Genome-wide association analysis identified splicing single nucleotide polymorphism in CFLAR predictive of triptolide chemo-sensitivity - Chauhan, Lata; Jenkins, Gregory D.; Bhise, Neha; Feldberg, Tanya; Mitra-Ghosh, Taraswi; Fridley, Brooke L.; Lamba, Jatinder K. (BMC genomics, 2015)
Triptolide is a therapeutic diterpenoid derived from the Chinese herb Tripterygium wilfordii Hook f. Triptolide has been shown to induce apoptosis by activation of pro-apoptotic proteins, inhibiting NFkB and c-KIT pathways, suppressing the Jak2 transcription, activating MAPK8/JNK signaling and modulating the heat shock responses. In the present study, we used lymphoblast cell lines (LCLs) derived from 55 unrelated Caucasian subjects to identify genetic markers predictive of cellular sensitivity to triptolide using genome wide association study. Our results identified SNPs on chromosome 2 associated with triptolide IC50 (p < 0.0001). This region included biologically interesting genes as CFLAR, PPIl3, Caspase 8/10, NFkB and STAT6. Identification of a splicing-SNP rs10190751, which regulates CFLAR alternatively spliced isoforms predictive of the triptolide cytotoxicity suggests its role in triptolides action. Our results from functional studies in Panc-1 cell lines further demonstrate potential role of CFLAR in triptolide toxicity. Analysis of gene-expression with cytotoxicity identified JAK1 expression to be a significant predictor of triptolide sensitivity. Overall out results identified genetic factors associated with triptolide chemo-sensitivity thereby opening up opportunities to better understand its mechanism of action as well as utilize these biomarkers to predict therapeutic response in patients.